RETRACTED: An empirical investigation between brand orientation and brand performance: Mediating and moderating role of value co-creation and innovative capabilities - Yueqiang, Zhao (Frontiers in Psychology, 2022)
This study analyses the function of value co-creation in mediating the relationship between brand orientation, brand performance, and innovation capacities in China's small and medium-sized enterprises (SMEs). Using the organization's size differential characteristic, additional testing of these criteria across disaggregated SME levels is performed. The empirical examination of 240 enterprises in an emerging market setting was conducted using Structure Equation Modelling (SEM). According to the results of the moderation and mediation research, value co-creation and capabilities often displayed positive moderating effects across all organization sizes, but they are conditional and not invariant when disaggregated by enterprise size. The research reveals that business owners and managers must decide the most successful complements to their brand orientation efforts based on the appropriate combinations of business abilities for the size of their particular firms.